Neutralization Studies with Marek's Disease Virus and Turkey Herpesvirus - Melchior, F. W. (1973)
Use of Marek's disease virus (MDV) in a neutralization test presents several problems, which are described, making this potentially useful test difficult. To obviate these difficulties, a plaque reduction test has been designed based on cross-neutralization of turkey herpesvirus (HVT) by serum-neutralizing MDV. The technique for such a neutralization test is outlined. Kinetics of development of neutralizing antibodies in chickens inoculated with HVT and MDV are described. The neutralization test can be used to evaluate viability of HVT vaccines and the possible role of neutralizing antibodies in the protection afforded by vaccination against MDV-induced tumors.